Case Report: Dacomitinib is effective in lung adenocarcinoma with rare EGFR mutation L747P and brain metastases - Li, Yibin; Guo, Weixi; Jiang, Bin; Han, Chengkun; Ye, Feng; Wu, Jingxun (Frontiers in Oncology, 2022)
Due to the low incidence of rare EGFR mutation, its response to EGFR-TKI has not been fully investigated. L747P is a rare EGFR mutation in EGFR exon 19. Previous case reports showed that patients with EGFR L747P mutation responded to afatinib treatment. However, we encountered a patient with EGFR L747P who resistant to afatinib but responded to dacomitinib. It is the first case report of the effective application of dacomitinib in a patient with L747P mutation and BMS, and the efficacy of BMS achieved PR.